ENHANCING STUDENT’S VOCABULARY BY USING JUMBLED-LETTER GAME IN ENGLISH LANGUAGE TEACHING - Fudhla, Nora (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2013)
This paper aims at discussing the ways to enhance student’s vocabulary by using jumbled-letter For some language teachers, teaching vocabulary is challenging, especially in English Language Teaching classroom. Nowadays, the teacher should provide a vocabulary teaching which avoiding vocabulary list memorization or vocabulary translation. Besides, the teacher also should consider about the students’ different ability to master vocabulary. Some language students may master new vocabulary faster than others and some of them may find many difficulties to master new vocabulary. On the other side, some students may master or memorize some vocabulary but they cannot spell the word correctly.